Like tears in rain - Tur Planells, Helena (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The hybridization between organic and inorganic produces a sinister emotion In the cyborg, the organic part claims its place in humanity, but we fail to grant it. Except in one case: that of Roy Baty, the Nexus–6 replicant of Do Androids Dream of Electric Sheep? and its film adaptation Blade Runner. In this article, we are going to find out why.